2019
DOI: 10.1590/2317-1782/20192018207
|View full text |Cite
|
Sign up to set email alerts
|

Atividade elétrica dos músculos masseter e supra-hióideo durante a deglutição do paciente com esclerose múltipla

Abstract: RESUMO Objetivo caracterizar a atividade eletromiográfica dos músculos da deglutição na EM. Método foram avaliados 60 indivíduos, sendo 30 com diagnóstico definitivo de EM e 30 sem alterações neurológicas. Foram levantados os dados pessoais dos voluntários e, em seguida, coletados em prontuário tempo de diagnóstico, forma clínica da doença e escore da escala EDSS. Em seguida foi administrado o questionário DYMUS. Todos foram submetidos à realização do Protocolo de Avaliação Eletromiográfica da Deglutição. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Literature on the association between MS and dysphagia is rapidly growing and previous studies have mentioned dysphagia as a common symptom of MS based on a number of techniques such as screening strategies, instrumental, non-instrumental, and clinical examinations. (5,16,24,(26)(27)(28)(29) Many articles also categorize dysphagia based on its severity into 5 classes including slight, alarming, mild, moderate, and severe, whereas others may choose to classify this disorder based on the anatomical location that is primarily affected, such as oral, oropharyngeal, pharyngeal, esophageal, etc. there are also neurogenic and functional types of dysphagia that are due to functional disturbances in the swallowing mechanisms rather than its anatomical structures.…”
Section: Discussionmentioning
confidence: 99%
“…Literature on the association between MS and dysphagia is rapidly growing and previous studies have mentioned dysphagia as a common symptom of MS based on a number of techniques such as screening strategies, instrumental, non-instrumental, and clinical examinations. (5,16,24,(26)(27)(28)(29) Many articles also categorize dysphagia based on its severity into 5 classes including slight, alarming, mild, moderate, and severe, whereas others may choose to classify this disorder based on the anatomical location that is primarily affected, such as oral, oropharyngeal, pharyngeal, esophageal, etc. there are also neurogenic and functional types of dysphagia that are due to functional disturbances in the swallowing mechanisms rather than its anatomical structures.…”
Section: Discussionmentioning
confidence: 99%
“…All SLH therapists who reported using EB do so with equipment manufactured by MIOTEC ® , which widely spreads SEMG research nationwide [23][24][25][26] . International studies on this topic use other brands, such as MyoTrac ®27 and VitalStim ® Plus 28 , which provide EB and neuromuscular electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, after rehabilitation, activation indexes of muscle modules become more similar between people with MS and healthy controls, indicating a potential positive impact of rehabilitation on muscle function 83 . Aside from that, previous electromyographic studies of swallowing in individuals with MS have revealed increased electrical activity in the masseter and decreased activity in the suprahyoid muscles 90 . These changes have been correlated with the Expanded Disability Status Scale (EDSS), suggesting their potential as clinical markers of disease severity.…”
Section: Emgmentioning
confidence: 94%
“…Furthermore, popular were contraction and extensions tasks [84][85][86][87] as well as reaching tasks 88,89 . EMG sensors have also been used to investigate dysphagia [90][91][92] . It is known and apparent that MS induces alterations in muscle synergies, leading to different activation patterns compared to healthy controls.…”
Section: Emgmentioning
confidence: 99%